THE IMPACT OF MEDICAL DISCOURSE: HOW LANGUAGE INFLUENCES THE HUMAN BODY AND FACILITATES HEALING - Burxonova Mohira Omonilla qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This research investigates the significant influence of medical discourse on both the physiological and psychological aspects of health. It explores how specific linguistic features in medical discourse, including language style, tone, and structure, can either support or hinder patient recovery. The study finds that language is a crucial factor in improving patient care, suggesting that healthcare providers should adopt empathetic, clear, and culturally sensitive communication strategies to enhance recovery and patient satisfaction.